Sensory Attenuation in the Auditory Modality as a Window Into Predictive Processing - Kiepe, Fabian; Kraus, Nils; Hesselmann, Guido (Frontiers in Human Neuroscience, 2021)
Self-generated auditory input is perceived less loudly than the same sounds generated externally. The existence of this phenomenon, called Sensory Attenuation (SA), has been studied for decades, and is often explained by motor-based forward models. Recent developments in the research of SA, however, challenges these models. We review the current state of knowledge regarding theoretical implications about the significance of Sensory Attenuation and its role in human behavior and functioning. Focusing on behavioral and electrophysiological results in the auditory domain, we provide an overview of the characteristics and limitations of existing SA paradigms, and highlight the problem of isolating SA from other predictive mechanisms. Finally, we explore different hypotheses attempting to explain heterogeneous empirical findings, and the impact of the Predictive Coding Framework in this research area.